Integration of Digital Technologies in Environmental Education: A Systematic Review of Trends, Impacts, and Future Directions - H. Husamah; Abdulkadir Rahardjanto; Tutut Indria Permana; Ahmad Adnan Mohd Shukri (Jurnal VARIDIKA, 2025)
The integration of digital technologies in environmental education (EE) has emerged as an important research area. However, a comprehensive synthesis of international research remains scarce. This systematic literature review (SLR), adhering to the PRISMA guidelines, aims to fill this gap by synthesizing peer-reviewed articles published in the past decade, specifically from the Scopus database. While the Scopus database was prioritized due to its comprehensive collection of high-quality, peer-reviewed journals in the field, future research should consider incorporating studies from other databases to ensure broader coverage of the topic. The primary objectives of this review are to analyze: (1) the predominant research approaches and instruments used in digital technology research in EE; (2) key findings regarding the application of digital technologies in EE; (3) thematic categories that explain the role of digital tools in environmental learning; and (4) the impact of digital technologies on promoting pro-environmental behavior through pedagogical integration. This review synthesizes current research practices and outlines how technologies such as augmented reality (AR), virtual reality (VR), and mobile applications enhance student engagement, environmental knowledge, and pro-environmental behavior. Additionally, the review explores the potential risks associated with the adoption of digital technologies, including the phenomenon of "techno-solutionism." It emphasizes the importance of culturally and ethically responsive pedagogies to mitigate these risks. Methodologically, the review adopts a critical approach, evaluating how different studies have addressed these challenges and suggesting strategies for responsible and context-aware implementation of digital tools in EE. The findings of this review underscore the need for critical thinking in the use of digital technologies in EE. The future of digital EE research should focus on long-term impact assessments and the integration of indigenous knowledge into digital pedagogies, ensuring a more inclusive and effective approach to environmental education.